ANGIOSOMAL APPROACH IN THE TREATMENT OF PURULENTNECROTIC COMPLICATIONS OF DIABETIC FOOT - Abdullayev Sayfulla Abdullayevich; Xujabaev Safarboy Tuxtabayevich; Makhmudov Timur Bahadirovich; Khudainazarov Utkir Rabbimovich; Larin Igor Vladimirovich (Scholar Express Journals, 2023)
In the developed countries of the world, up to 5-6% of the population suffers from a complication of diabetes mellitus. Complications associated with surgical infection in diabetic patients account for up to 30-40% of the total number of surgical patients. Gangrene of the toes and feet in general is 17 times more likely to develop in diabetic patients than in people who do not have diabetes. In recent years, when choosing a method of surgical treatment of patients with purulent-necrotic complications of diabetic foot syndrome (DFS), preference is given to the use of angiosomal approaches.
Keywords: preference; diabetic; syndrome; population